Efeito das condições de resfriamento após a laminação a quente sobre a microestrutura e propriedades mecânicas de um aço bifásico da classe de resistência de 800 MPa - Kairo de Barros Guimarães (2019)
Dual phase (DP) steels show an excellent combination between high mechanical strength and good ductility. Their microstructure consists basically of martensite islands, of high strength, dispersed in a soft and ductile ferritic matrix. In hot rolled steels this microstructure is defined by the cooling conditions after the last rolling pass. The effect of the cooling conditions on the microstructure and hardness of a dual phase hot-rolled steel 800 MPa strength was investigated. Simulations of the cooling conditions using a dilatometer were carried out from samples of a hot rolled coil with variations of the intermediate temperature from 620 to 740°C, reheating at isothermal holding time between 1 and 10 s and coiling temperature between 50 to 400°C. In addition, two CCT diagrams were developed to evaluate the effect of the isothermal holding time on the phase transformations of the remaining austenite. It was observed that the intermediate temperature has a strong influence on the kinetic of the phase transformation, as well as the isothermal holding time influences the amount of ferrite formed and, consequently, the final microstructure and hardness of the material. The coiling temperature did not cause significant changes in the amount and morphology of the ferrite, but a gradual replacement of martensite with bainite was observed, which, in addition to the self-tempering effect, contributed to the reduction of hardness values.